The Study of E-Government Implementation in Indonesia - Kadek Ayu Fitri Aryanti; I Made Sukarsa; Anak Agung Ngurah Hary Susila (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi), 2021)
The Development of information technology make a huge impact in various aspects of life. One of the biggest influences given by information technology is in government. Indonesia as a country that consists of various provinces are in great need of advancement in information technology. Advances in technology provide convenience to government institutions to coordinate with each other to help Indonesia become more advanced. Sistem Pemerintahan Berbasis Elektronik or SPBE is one example of advances in information technology that has been used by the government to provide the best service to its users. Before the SPBE there was a different term, which was E-Government. E-Government is one of the information technologies used by the government to provide services and information to public, people in business, as well as other matters related to government affairs. This study aims to determine the development of the implementation of E-Government in Indonesia, the concept of E-Government in Indonesia and the comparison of Indonesian E-Government with other countries. Keywords: Information Technology, History, Sistem Pemerintahan Berbasis Elektronik, E-Government